2013
DOI: 10.1186/scrt232
|View full text |Cite
|
Sign up to set email alerts
|

Isolation method and xeno-free culture conditions influence multipotent differentiation capacity of human Wharton’s jelly-derived mesenchymal stem cells

Abstract: IntroductionHuman Wharton’s jelly (WJ) has become a preferred source of mesenchymal stem cells (MSCs) whose clinical applications are limited by the use of adequate xeno-free (XF), in vitro manipulation conditions. Therefore, the objective of our study was to characterize WJ-derived MSCs (WJ-MSCs), isolated by different methods and cultured in a commercially available, MSC XF medium, not least of all by investigating their endothelial differentiation capacity.MethodsWJ explants and enzymatically dissociated WJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 66 publications
4
51
0
Order By: Relevance
“…Nevertheless, we observed low adipogenic induction, a characteristic which has already been reported in the literature for UCM-MSCs, when compared with MSCs from other sources, such as the bone-marrow [53].…”
Section: Discussionsupporting
confidence: 60%
“…Nevertheless, we observed low adipogenic induction, a characteristic which has already been reported in the literature for UCM-MSCs, when compared with MSCs from other sources, such as the bone-marrow [53].…”
Section: Discussionsupporting
confidence: 60%
“…However, foreseeing the therapeutic use of these cells, efforts are being made to avoid the use of FBS because of the high risk of contamination (virus, prion), potential to promote xenogeneic immune reactions (Bieback, ) and the ethical issues associated with the harvesting and collection of this animal‐derived product (Gstraunthaler, ). In this context, several groups, including the present authors, have demonstrated the ability to isolate and expand UCM MSCs in planar tissue culture systems using more defined serum‐/xenogeneic(xeno)‐free culture medium preparations (Corotchi et al , ; Simões et al , ; Swamynathan et al , ). Others have tested the use of human blood‐derived platelet lysate (HPL) products as culture medium supplements for this purpose.…”
Section: Introductionmentioning
confidence: 86%
“…The cardiovascular system has low regenerative potential, which makes the use of WJ-MSCs an ideal alternative in cardiovascular tissue repair with their immunomodulatory properties and self-regenerating capacity [26]. Interestingly, biologically active heart valve leaflets could be engineered using only cells from the human umbilical cord [27].…”
Section: Cell Therapy For Cardiovascular and Connective Tissue Repairmentioning
confidence: 99%